Are acute infusion reactions after rituximab underreported? - Mohan, Prafull; Nazar, Shah; Gupta, Pooja (International Journal of Research in Medical Sciences, 2019)
Background: Rigorous premarketing trials may fail to capture safety issues associated with new drugs. This is more likely to happen in case of biopharmaceuticals. We take the case of rituximab, and anti CD20 monoclonal antibody, which was the first monoclonal antibody to get approval. This open label observational study was done with the objective of estimating the incidence of acute infusion reaction associated with rituximab infusion. Methods: The study population consisted of patients hospitalized for receiving rituximab, in day care centre(s) of a tertiary care hospital. Number and type of acute infusion reactions (AIR) were recorded on a case record form along with patient characteristics and medical history. Results: A total of 50 infusions were observed and all infusions were followed by at least one AIR. Total 71 AIRs were recorded among these 50 infusions (1.4 AIR per infusion). Non-Hodgkin’s lymphoma was the commonest indication for which patients were receiving rituximab. In a subset analysis, incidence of AIR was statistically lower in patients having received corticosteroids as premedication. However, brand of rituximab, gender of the patient and first or second cycle had no bearing on incidence of AIRs. Conclusions: AIRs are more common in real time clinical settings than what is reported. There is a need to formulate appropriate risk management plan depending on post marketing clinical data. Use of corticosteroids as premedication may be one such strategy. New drugs, esp biopharmaceuticals, may have unidentified/under reported safety issues and there is a need to undertake focussed pharmacovigilance endeavours to unravel them.